Kelayakan Berita Citizen Journalism - Olivia Putri Andini; Hani Nur Rizka; Muawanah Aliyah; Noerma Kurnia Fajarwati (Pusat Riset dan Inovasi Nasional, 2024)
The suitability of citizen journalism news is becoming an increasing concern in the current digital era. Citizen journalism, or citizen journalism, refers to the practice of ordinary people voluntarily participating in the process of delivering news and information through online platforms, such as social media or citizen news websites. In this context, the newsworthiness of citizen journalism is a crucial question because of its increasing influence in shaping public opinion and influencing information narratives. The credibility of news is greatly influenced by the reputation and integrity of the information source. In the context of citizen journalism, credibility can be questioned due to the lack of a strict editorial process and quality control which tends to be looser compared to traditional news media. Therefore, research and evaluation of the reputation and accuracy of information sources is important in determining the suitability of citizen journalism news.